The Role of Homeroom Teachers in Addressing the Negative Influence of Smartphones on Elementary School Students - Yuli Asmarani; Yopi Malagola (Edelweiss : Journal Of Innovation In Educational Research, 2026)
The massive penetration of smartphones among elementary school-aged children demands the strengthening of the role of homeroom teachers as the primary companions of students in the school environment. This study aims to analyze the role of homeroom teachers in addressing the negative influence of smartphones on upper-grade elementary school students in Cluster 1 Labuhan Ratu. This study used a quantitative descriptive approach with a population of all upper-grade homeroom teachers (grades IV, V, and VI) in Cluster 1 Labuhan Ratu, totaling 72 people. The research sample was determined using purposive sampling of 36 homeroom teachers, and data were collected using a questionnaire instrument. The results showed that the role of homeroom teachers in addressing the negative influence of smartphones was in the moderately influential category, with 64% (23 of 36 respondents) of homeroom teachers in that category, while 28% were in the influential category and 8% were in the less influential category. This finding confirms that the role of homeroom teachers is already running but is not optimal, so strengthening the competence of homeroom teachers in accompanying students in facing digital risks in the smartphone era is still needed.